Cell Phone Ownership and Cellular Text/Email Capabilities Among Temporary and Payroll Construction Workers - Caban-Martinez, Alberto J.; Moore, Kevin J.; Chalmers, Juanita J.; Santiago, Katerina M.; Baniak, Melissa; Jordan, Melissa M. (Frontiers in Public Health, 2020)
Background: With high rates of temporary workers and a transient worker population, the U.S. construction workforce presents a challenge for long-term research and outreach activities. Increasing availability of affordable cell phone technologies may provide an opportunity for research follow-up among construction workers once they leave the worksite. Using pilot study survey data we characterize and examine the association of cell phone technology ownership and cellular text/email services among a non-probabilistic sample of payroll and temporary construction workers. Methods: A cross-sectional study design was used to administer a one-time paper-based anonymous survey to construction workers working at construction sites in Florida, USA. The survey featured questions on sociodemographic characteristics, occupational history, cell phone technology ownership, and cellular text/email services capabilities. Results: Among the 223 construction worker survey respondents, 31.4% identified as temporary workers and 68.6% were on payroll and 87.4% owned a cell phone. Construction workers who own a cell phone had greater than a high school education (28.9% vs. 25.0%; p=0.019), made >$30,000/year (27.1% vs. 14.8%;p=.011), had same cell phone number for >1-year (74.4% vs. 40.7%;p=0.001), and were employed as a payroll worker (71.0% vs. 50.0%;p=0.037). Temporary construction workers compared to their payroll counterparts were significantly less likely to have email services on their cell phone (unadjusted-odds ratio 0.41 [95% CI:0.17-0.97]). Conclusion: Cell phone ownership and smartphone-enabled technologies such as email/texting capabilities are higher among payroll than temporary construction workers. Further research on the frequency of cell phone use and types of email/texting services used by construction workers are needed.